Energy and protein requirements of male and female saanen goats - Figueiredo, Fernanda Oliveira de Miranda [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The objective of this research was to estimate, using the comparative slaughter technique, energy and protein requirements for maintenance and growth of castrated males, intact males and females Saanen goat kids between 15 and 30 kg of body weight and to evaluate the models from AFRC (1998) and NRC (2007) for predicting dry matter intake (DMI) and average daily gain (ADG) of growing goats. To determine net energy and net protein requirements for maintenance 25 castrate males, 26 intact males and 24 females were used, where 7 castrated males, 8 intact males and 6 females were randomly selected to estimate the initial empty body composition. The remaining animals, 18 castrate males, 18 intact males, and 18 females were used with dietary treatments that consisted of 3 levels of intake: ad libitum, 75% and 50% of ad libitum intake. Within each sex, six blocks of 3 animals each were formed. Within each block, one animal was randomly assigned to each level of intake. Thus, pair feeding was established within each block based on the intake of the animal fed ad libitum. All animals within a block were slaughtered when the animal fed ad libitum reached 30 kg of BW. The 75 and 50% of ad libitum rationing were determined daily based on the DMI of the animal fed ad libitum on the previous day. The net energy and net protein requirements for gain (NEg and NPg, respectively) were obtained using 20 castrated males, 20 intact males and 18 females. The animals were fed ad libitum and slaughtered at targeted BW of 15, 23, and 30 kg. We found that sex did not affect energy and protein requirements for maintenance as well as protein requirements for growth. However it affected energy requirements for growth where castrated males and females had the same NEg comparing with intact males. To evaluate the models from AFRC (1998) and NRC (2007) for predicting DMI and ADG of growing goats, individual data of 37 Saanen goat kids (12 intact males, 13 castrated ...

Os objetivos deste trabalho foram estimar, utilizando a técnica do abate comparativo, as exigências de energia e proteína para mantença e crescimento de caprinos Saanen, machos inteiros, machos castrados e fêmeas com peso corporal variando de 15 a 30 kg e, avaliar os modelos do AFRC (1998) e NRC (2007) para predizer o consumo de matéria seca (CMS) e ganho de peso (GP) de caprinos Saanen em crescimento. Para determinar as exigências líquidas de energia e proteína para mantença foram utilizados 25 machos castrados, 26 machos inteiros e 24 fêmeas. Destes, sete machos castrados, oito machos inteiros e seis fêmeas foram selecionados aleatoriamente e abatidos com 15 kg de peso corporal para a estimativa da composição corporal inicial. Os animais restantes, 18 machos castrados, 18 machos inteiros e 18 fêmeas foram distribuídos nos tratamentos, que consistiram de três níveis de ingestão: ad libitum, 75% e 50% do consumo ad libitum. Dentro de cada sexo, foram formados seis blocos de três animais e dentro de cada bloco, os animais foram distribuídos aleatoriamente em cada nível de ingestão. Assim, a alimentação foi estabelecida dentro de cada bloco com base no consumo dos animais alimentados ad libitum. Todos os animais dentro de um bloco foram abatidos quando o animal alimentado ad libitum atingiu 30 kg de peso corporal. A quantidade a ser fornecida aos animais submetidos aos tratamentos 75 e 50% do ad libitum foi determinada diariamente com base no CMS do animal alimentado ad libitum no dia anterior. As exigências de energia e proteína para crescimento foram obtidas usando 20 machos castrados, 20 machos inteiros e 18 fêmeas. Os animais foram alimentados ad libitum e abatidos aos 15, 23 e 30 kg de peso corporal. O sexo não afetou as necessidades de energia e proteína para mantença, bem como as exigências de proteína para o crescimento. No entanto, afetou as necessidades energéticas para o crescimento no qual ...
Keywords: Caprino; Corpo - Composição; Crescimento; Alimentos - Consumo; Corpo - Peso; Growth